TRADISI MESOKO PADA MASYARAKAT TOLAKI (Studi di Desa Lamoen Kecamatan Angata Kabupaten Konawe Selatan) - Asniatin, Asniatin; Barlian, H. (Jurnal Penelitian Pendidikan Sejarah UHO, 2020)
ABSTRACTThis study aims: 1) To describe the background of the implementation of the Mesoko tradition in the Tolaki community in Lamoen Village, Angata District, South Konawe Regency; 2) To describe the implementation system of the Manado tradition in the Tolaki community in Lamoen Village, Angata District, South Konawe Regency; 3) To describe the function of the Mesoko tradition in the Tolaki community in Lamoen Village, Angata District, South Konawe Regency. The method used in this research is descriptive qualitative research method with the following stages: 1) data collection techniques, 2) data analysis techniques, 3) data validity. This research literature review uses the concept of tradition, the concept of Mesoko, the concept of community solidarity, relevant research and framework. The results of this study are: (1) The background for the implementation of the Mesoko tradition is the belief that the Mesoko tradition has existed since the time of the ancestors, which is often done so that it has become a tradition of the Tolaki people which is still maintained today and is upheld by the people of Lamoen Village. The Mesoko tradition is not only carried out by the less fortunate but even officials can carry out the Mesoko cultural tradition. (2) The system for implementing the Mesoko tradition, namely by first notifying the village government or village officials to determine the date for the implementation of the Mesoko tradition, it is only necessary to prepare invitations to be distributed by traditional leaders or community leaders who are responsible for disseminating it in the community, preparing food and drinks for served when the Mesoko tradition is in progress, each family will have a separate bookkeeping to record the large and small amounts of money and bring a pack of cigarettes that are placed on the side and wrapped in cloth to be offered to the head of the household then they are told the place, time and date of the implementation of this Mesoko tradition. . (3) The functions of the Mesoko tradition in the Tolaki community in Lamoen Village, namely: (a) As a place to unite kinship because almost all families and communities as a whole participate in the implementation of the Mesoko tradition. (b) As a means of solidarity because it involves all elements of society to participate in carrying out the Mesoko tradition, there is a sense of caring, help, and mutual cooperation. (c.) Fulfillment of needs because there will be a sense of satisfaction that is received, both material satisfaction so that there is sufficient money to carry out a wedding or celebration because it has first carried out the Mesoko tradition.Â